Revolutionary diplomats? Introduction to the study of North African foreign policies within the context of the Arab Spring. Issue 4 (4th July 2019) - Schraeder, Peter J.; Endless, Brian; Schumacher, Michael J.; Lynn Dobbs, Kirstie
ABSTRACT: This article explores the concept of 'revolutionary diplomats' that is central to this guest-edited issue of The Journal of North African Studies . Specifically, we explore whether the political openings associated with the Arab Spring beginning in January 2011 have permitted the emergence and/or re-emergence of state and non-state actors that are capable of challenging the foreign policy supremacy of authoritarian presidents, and therefore playing more important roles in the formulation and implementation of their countries' foreign policies. We do so by focusing on the North African countries of Algeria, Egypt, Libya, Morocco and Tunisia. The first part of this article explores North Africa's status within the Arab Spring and broader Foreign Policy Analysis literatures, most notably the foreign policy shortcomings associated with an inherently case study approach that dominates these literatures. A second section examines three theoretical approaches ('big man', great power, and dependency theories) that typically have been adopted to explain North African foreign policies. The primary dilemma with these theories is that they limit our understanding of North African foreign policies to either North African rulers or external powers. A third section sets out a domestic actor approach to North African foreign policy, which underscores that a host of state actors (such as the Ministry of Foreign Affairs) and non-state actors (such as civil society groups) play varied foreign policy roles. The foreign policy influence of these actors has ebbed and flowed during democratic and authoritarian periods alike, including during the Arab Spring.